Tracheotomy management : a multidisciplinary approach - Seidman, Peggy A., 1959-; Sinz, Elizabeth; Goldenberg, David, 1962- (Cambridge : Cambridge University Press, 2011)
Patients with tracheotomies are managed by a wide variety of healthcare professionals. As a result, information regarding best practice is scattered throughout the medical literature and can be difficult to identify and implement in the clinical setting. Tracheotomy Management: A Multidisciplinary Approach is a practical review of all tracheotomy procedures and acute and chronic tracheotomy care. It combines evidence-based practice and expert opinion to create an invaluable hands-on guide for any healthcare provider managing patients with tracheotomies. Each chapter is authored by at least two different subspecialists, contains case studies with real-life examples of problematic clinical scenarios, and is enhanced by high quality images. The rationale for different approaches is discussed to guide the decision-making process. Written and edited by tracheotomy experts from a wide variety of disciplines, Tracheotomy Management: A Multidisciplinary Approach is essential reading for anesthesiologists, nurse anesthetists and critical care and emergency physicians.
Anatomy of the anterior and lateral neck / Eliot Regenbogen -- Elective surgical tracheotomy in the adult -- Yvonne Tsui, Michael Ondik, and David Goldenberg -- Percutaneous tracheotomy / Garret Choby, Dmitri Bezinover, and David Goldenberg -- Emergency surgical airways / Leonard Pott and Scott Goldstein -- Congenital, embryological, and anatomic variations, and their association with pediatric tracheotomy / Elliot Regenbogen -- Pediatric tracheotomy / Robert Yellon, Raymond Maguire, and Jay B. Tuchman -- Laryngotracheal reconstruction: surgical management of pediatric airway stenosis / Diego Preciado, Sophie R. Pestieau, and Ira Todd Cohen -- Timing of tracheotomy for intubated patients / Alison Wilson ... [et al.] -- Intensive care unit tracheotomy care / Shaji Poovathoor ... [et al]. -- Complications of tracheotomy / Steven L. Orebaugh -- Airway manipulation with tracheotomy / Daryn H. Moller ... [et al.] -- Tracheotomy equipment / Dana Stauffer, John Stene, and Joanne Stene -- Care of the patient with a tracheotomy / Margaret Wojnar and Jonathan D. McGinn -- Tracheotomy education for home care / Jodie E. Landis, Michael K. Hurst, and Brian W. Grose.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Tracheotomy -- Patients -- Care; Trachea -- Surgury